Performance Of Different Hyv Mustard Varieties With Sugarcane (Saccharum officinarum) As Intercrop In Farmers Fields (Bangladesh Journal of Agricultural Research, 2013)
A field experiment was conducted at farmers field of Kushtia Sadar upazila under Kushtia district during the period from November 2009 to January 2012 to find out suitable mustard varieties for intercropping with sugarcane. Five rapeseed/mustard varieties viz., Improved Tori -7, BARI Sarisha-9, BARI Sarisha-11, BARI Sarisha-14 and BARI Sarisha-15 were intercropped with sugarcane. Results showed that different intercropping combinations significantly influenced yield and yield components of mustard. The mustard variety BARI Sarisha-11 produced the highest seed yield (2199 kg/ha). Mustard varieties in intercropped situation depressed cane yields by 2.79-9.96% compared to sole cane yield. The highest cane equivalent yield (111.28 t/ha) was recorded in sugarcane + mustard var. BARI Sarisha-11 combination. The highest gross return (Tk. 633098/ha), gross margin (Tk. 518078/ha) and benefit cost ratio (5.50) were also obtained from the same combination which was followed by sugarcane + mustard var. BARI Sarisha-14 combination. The results revealed that BARI Sarisha-11 or BARI Sarisha-14 might be grown with sugarcane as intercrop in Kushtia area for getting maximum profit. Bangladesh J. Agril. Res. 38(2): 211-217, June 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i2.15884